SYSTEMATIC ANALYSIS OF LITERATURE ON SOCIAL FACTORS AS DETERMINANTS OF STUDENT MOTIVATION IN PARTICIPATION IN IPS COMPETITIONS AT JUNIOR HIGH SCHOOL LEVEL - Astuti, Sri; Adha, Muhammad Mona; Wahyudi, Apri (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2025)
This study aims to examine the social factors that influence junior high school students’ motivation to participate in social science competitions in Bandar Lampung City. Using the systematic literature review (SLR) method, this study collected and analyzed various relevant journals and articles from 2000 to 2025. The results showed that social factors, such as family support, peers, school environment, and the role of teachers, have a significant influence on students’ learning motivation and participation in social studies competitions. Support from the social environment can increase students’ self-confidence, foster a spirit of healthy competition, and strengthen intrinsic motivation. Conversely, excessive pressure and lack of psychosocial support can reduce students’ motivation to participate. Strategies to increase motivation should involve the active role of all social elements around students and create a positive and fun learning atmosphere. These findings provide important implications in the development of learner coaching programs that are able to increase active participation in social and psychologically based academic competitions